Mathematical Formulation for Prediction of Structural Performance of Green Geopolymer Concrete Beams and Columns - et. al., Arunkumar K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to minimise the environmental impact of the waste and its disposal processes and to reduce global warming by cement production, this study has focused on the demand. This research looked at how waste wood ash can be used to make geopolymer concrete beams and columns, which can be used to replace traditional reinforced concrete elements in the construction industry. Waste wood ash, a waste produced in the nearby hotel and manufacturing factories by burning the waste wood collected in the woodworking industry and throwing the ash to land causing considerable environmental pollution. Geopolymer is an innovative inorganically friendly, alkaline-based binding agent that stimulates the source material of aluminosilicate (such as metakaolin, fly ash and GGBS). For three types of concretes (30 percent WWA – 70 percent Fly ash Geo-polymer concrete, Fly ash Geo-polymer concrete, and Reinforced Cement Concrete), the mathematical formula for the behaviour of beams in deflection, ductility factor, flexural strength, and columns in load carrying ability, stress strain behaviour, and load-deflection behaviours were investigated in this study. The results showed that the inclusion of waste wood ash into geopolymer concrete contributed to the 42 and 28 percent increase of the capacity for beam and column. Furthermore, by replacing waste wood ash, the compotation of structural elements was improved in their rigidity and ductility. The derived mathematical equations were most suitable for the prediction of forecast.